Cell-type specific regulation of cortical excitability through the allatostatin receptor system - Ikrar, Taruna; Shi, Yulin; Velasquez, Tomoko; Goulding, Martyn; Xu, Xiangmin (Frontiers in Neural Circuits, 2012)
Recent technical advances enable the regulation of neuronal circuit activity with high spatial and temporal resolution through genetic delivery of molecular activation or inactivation systems. Among them, the allatostatin receptor (AlstR)/ligand system has been developed for selective and quickly reversible silencing of mammalian neurons. However, targeted AlstR-mediated inactivation of specific neuronal types, particularly diverse types of inhibitory interneurons, remains to be established. In the present study, we achieved Cre-directed expression of AlstRs to excitatory and inhibitory cell types in the cortex, and found that the AlstR-mediated inactivation was specific and robust at single cell and neuronal population levels. Bath application of the allatostatin peptide markedly reduced spiking activity of AlstR-expressing excitatory and inhibitory neurons in response to intrasomatic current injections and laser photostimulation via glutamate uncaging, but control neurons without AlstR expression were not affected. As for the cortical network activity, the peptide application constrained photostimulation-evoked excitatory activity propagation detected by fast voltage-sensitive dye (VSD) imaging of the slices expressing AlstRs selectively in excitatory neurons, while it augmented excitatory activity in those slices with inhibitory neurons expressing AlstRs. In addition, AlstR-mediated inactivation effectively suppressed pharmacologically-induced seizure activity in the slices targeting AlstRs to excitatory neurons. Taken together, our work demonstrated that the genetic delivery of AlstRs can be used for regulation of cortical excitability in a cell-type specific manner, and suggested that the AlstR system can be potentially used for fast seizure control.